The Citizen On Trial: The New Confession Rules - Kamisar, Yale (1967)
Commenting on why it has taken the United States so long to apply the privilege against self-incrimination and the right to counsel to the proceedings in the stationhouse as well as to those in the courtroom - as the Supreme Court did in Miranda v. Arizona - this author notes that, To a large extent this is so because here, as elsewhere, there has been a wide gap between the principles to which we aspire and the practices we actually employ